Assessment of indoor air quality for closed cafés in Baghdad City, Iraq - Mohammed Abdul Bari Fezea; Maha A. Gathwan (Caspian Journal of Environmental Sciences)
The phenomenon of young people frequenting closed cafes spread in Baghdad to smoke hookahs and cigarettes has increased. This phenomenon is associated with unemployment, an increase in leisure time and the deterioration of economic conditions. This phenomenon has an impact on indoor air quality and exposes workers to the risk of exposure to various pollutants, including particulate matter, therefore, we examined some indicators (PM2.5, PM10) IAQ for a month in summer and another month in winter in six different locations in the Rusafa district. PM2.5 and PM10 concentrations, relative humidity (RH) and temperatures were measured using (Multifunction Air Quality Detector BENETECH -China). The results showed an increase in temperatures inside closed cafes, exceeding the recommended limits, and regardless of the seasonal fluctuations, the average concentrations of both PM2.5 and PM10 inside closed cafes for the months of August and December exceeded the daily and annually PM standards recommended by World Health Organization for both PM2.5 and PM10 concentrations were higher in summer than in winter were the most of young people enjoy a long holiday.  The peak of PM2.5 and PM10 concentrations also occurred during evening rush hour, more than the highest readings in the morning periods.